CARA MENENTUKAN DAYA YANG DIGUNAKAN AIR CONDITIONING (AC) UNTUK KENDARAAN - Najamudin Najamudin (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
Vital transportation facilities for the community to facilitate and accelerate human movement from bed more quickly, safely and comfortably. Buses with large capacity with passengers over 50 people operating between cities or between provinces require specific performance in order to provide security and comfort for passengers on the way. Bus transports between cities and between provinces are equipped with air conditioning  system (AC) and some are not. In Buses that use air refreshments there is also no use of the standard main components installed from the manufacturer; such as compressors, condensers, expansion valves and others. Compressors in the air refreshing system can be analogous to the heart of the human body, which serves to suck and pump coolant (refrigerant) that circulates in the system. In this study found that there are several buses that compressor is not a standard compressor from the manufacturer. For that purpose, calculations are mainly carried out on cooling loads, achievement coefficients and compressor power.